Perlindungan Hukum Melalui Restitusi Terhadap Anak Korban Kejahatan Seksual (Penelitian Di Kabupaten Aceh Jaya) - Erlin Ritonga; Mohd. Din; Sulaiman Sulaiman (Universitas Medan Area, 2021)
This research aims to provide legal protection for child victims of crime through restitution as mandated in the law. Presidential Regulation (Perpres) Number 75 of 2020 concerning the Implementation of the Rights of Child Victims and Witness Children. The Presidential Regulation is a direct mandate of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. In terms of suffering or material loss experienced by the victim as a result of a criminal act committed by another person, it is appropriate that the perpetrator of the criminal act (the other person) provides compensation. Restitution to victims of crime in the context of the relationship between the perpetrator and the victim, is a manifestation of the resocialization of the responsibility of the perpetrator as a citizen. Through the resocialization process, it is intended and expected to instill a sense of social responsibility in the perpetrator, so that the value of restitution in this case does not lie in its efficacy in helping victims, but serves as a tool to make the perpetrators of criminal acts more aware of their